Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

HELP ASAP!!!!!!!!!!!!!! ITS AN EMERGENCY!!!!!!!!

Simplify the expressions
(24m^-2n)(1/4mn)

(4a^-2)^4

(9ab^-5)^-2


Sagot :

The simplified expression are as follows:

[tex](24m^{-2}n )(\frac{1}{4}mn ) =6m^{-1} n^{2}[/tex]

[tex](4a^{-2} )^{4} =4a^{-8}[/tex]

[tex](9ab^{-5} )^{-2} =9ab^{10}[/tex]

How to simplify an expression?

The expression can be simplified as follows;

using law of indices,

[tex](a^{x} )^{y} = a^{xy}[/tex]

Therefore,

[tex](24m^{-2}n )(\frac{1}{4}mn ) = \frac{24}{4} m^{-2+1} n^{1+1} =6m^{-1} n^{2}[/tex]

[tex](4a^{-2} )^{4} =4a^{-8}[/tex]

[tex](9ab^{-5} )^{-2} =9ab^{10}[/tex]

learn more on expression here: https://brainly.com/question/5232323

#SPJ1